2014
DOI: 10.1002/2014jc009911
|View full text |Cite
|
Sign up to set email alerts
|

The precursors in the Intra-Americas Seas to seasonal climate variations over North America

Abstract: In this paper, we show from observations that the Intra-American Seas precursor as characterized by the onset of the Atlantic Warm Pool (AWP; defined by the area enclosed by 28.5 C isotherm in the tropical Atlantic Ocean) has discernible impact on the boreal summer and fall seasonal climate variations over North America, a season and a region well known for relatively poor seasonal predictability. The onset of the AWP season is objectively defined as the day when the daily anomaly of the AWP area, west of 50 W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…However, the 2014 AWP appeared early in April. This is consistent with the recent study (Misra et al 2014) which demonstrates that the onset date of the AWP during ranged from late April to early August. The 2014 AWP was also distinctive in that the AWP was unusually large in November compared with the climatological AWP.…”
Section: H Atlantic Warm Pool-c Wangsupporting
confidence: 93%
“…However, the 2014 AWP appeared early in April. This is consistent with the recent study (Misra et al 2014) which demonstrates that the onset date of the AWP during ranged from late April to early August. The 2014 AWP was also distinctive in that the AWP was unusually large in November compared with the climatological AWP.…”
Section: H Atlantic Warm Pool-c Wangsupporting
confidence: 93%
“…AWPs coincide with the warm and cool phases of the Atlantic multidecadal oscillation (AMO; Delworth and Mann 2000;Enfield et al 2001). A recent study showed that the equatorial Amazon rainfall during the austral summer is negatively related to the following boreal summer's AWP SST, manifesting the remote ENSO impact on the AWP SST through its modulation of the Amazon rainfall (Misra and DiNapoli 2013). Wang et al (2008b) showed that the influences of the AMO on TC activity and climate might operate through the atmospheric changes induced by the AWP.…”
Section: H Atlantic Warm Pool-c Wangmentioning
confidence: 99%
“…The AWP displays a very strong seasonal cycle, with the AWP area peaking in August-September-October (ASO) season. This allows, following Misra et al (2014), objective definition of the onset of the AWP season based on the first day when the daily area of the AWP exceeds the climatological annual mean area of the AWP. Similarly, the demise of the AWP season is defined as the first day after the onset of the AWP season when the daily area of the AWP falls below the climatological annual mean area of the AWP.…”
Section: A Intra-american Seasmentioning
confidence: 99%
“…Similarly, the demise of the AWP season is defined as the first day after the onset of the AWP season when the daily area of the AWP falls below the climatological annual mean area of the AWP. Based on these definitions, Misra et al (2014) timescales. The variability of the AWP has been associated with corresponding warm season variations of North American precipitation cycles (C. Wang et al 2006Misra et al 2011Misra et al , 2014.…”
Section: A Intra-american Seasmentioning
confidence: 99%
See 1 more Smart Citation